Diagnosis, evaluation and management of osteoporosis in chronic kidney disease: navigating treatment approaches – Indian consensus statement - Kher, Vijay; Sharma, Rajkumar; Abraham, Georgi; Shah, Bharat; Gang, Sishir; Gulati, Sanjeev; Sahay, Manisha; Kothari, Jatin; Kumar BT, Anil; Ramachandran, Raja; Kalra, Sanjay; Sahay, Rakesh Kumar; et al. (Frontiers in Nephrology, 2025)
BackgroundManaging osteoporosis (OP) in chronic kidney disease (CKD) presents significant challenges due to altered bone metabolism. Given the lack of robust clinical trial data and a notable knowledge gap exists among nephrologists regarding an optimal management in this population, an expert consensus is crucial for developing tailored management strategies. This study aimed to gather an expert opinion to bridge this gap and establish consensus recommendations on the diagnosis and management of osteoporosis in CKD patients.MethodsA panel of 13 Indian and 1 international experts, including nephrologists and endocrinologists, participated in a structured survey and discussion process. Thirteen Indian experts provided their opinion on key clinical issues, including screening, diagnosis, and treatment strategies for osteoporosis in CKD. Consensus was achieved in a single round of voting, and recommendations were formulated based on the level of agreement among the panelists.ResultsThe expert panel reached a strong consensus (80-100% agreement) on several critical recommendations. It was agreed that osteoporosis in CKD is often asymptomatic, with fragility fractures being less common, and thus, early screening using dual-energy X-ray absorptiometry (DXA) is essential. The panel emphasized the importance of evaluating bone turnover status using serum biomarkers such as bone-specific alkaline phosphatase (BSAP) and intact parathyroid hormone (iPTH) to guide treatment decisions. Tailored treatment strategies were recommended, with a judicious use of bisphosphonates and denosumab, depending on the patient’s estimated glomerular filtration rate (eGFR) and bone turnover state. The management of renal osteodystrophy (ROD) was deemed necessary before addressing CKD-induced osteoporosis.ConclusionThis expert consensus provides critical insights and guidance for the management of osteoporosis in CKD. The recommendations emphasize individualized treatment approaches, the importance of early screening, and the integration of multidisciplinary care. These findings aim to fill existing knowledge gaps and improve clinical outcomes for CKD patients with osteoporosis.